Ischemia induced repolarization dispersion changes and ventricular arrhythmia: Validation of Frank vectorcardiography parameters: A review - Lennart Bergfeldt, MD, PhD; Lennart Gransberg, MSc, PhD; Gunilla Lundahl, MSc (Heart Rhythm O2)
Changes in dispersion of ventricular repolarization is a salient electrophysiological feature of acute myocardial ischemia and linked to life-threatening arrhythmias. In 9 studies, we applied Frank vectorcardiography not only for noninvasive monitoring of cardiac electrophysiology during acute ischemia induced during percutaneous coronary interventions, during clinical myocardial infarction, and in an occlusion-reperfusion pig model, but also for prognostic purposes after coronary events. Myocardial ischemia was in humans and pigs associated with significant changes in the ST segment, Tamplitude, Tarea, ventricular gradient, and T vector loop morphology. In the pig model, a link between dispersion changes and the occurrence and suppression (by spinal cord stimulation) of ventricular arrhythmias was found. Prognostically, after recent acute coronary events, the spatial peak and mean QRS-T angles were superior. In summary, vectorcardiography-based parameters were validated as reflecting changes in repolarization dispersion during myocardial ischemia in humans and pigs, and in pigs linked to the occurrence and suppression of ventricular arrhythmias.